The new silk roads : the present and future of the world - Peter Frankopan (London, England : Bloomsbury Publishing, 2018)
When The Silk Roads was published in 2015, it became an instant classic. A major reassessment of world history, itcompelled us to look at the past from a different perspective. The New Silk Roads brings this story up to date, addressing the present and future of a world that ischanging dramatically. Following the Silk Roads eastwards,from Europe through to China, by way of Russia and the Middle East, The New Silk Roads provides a timely reminderthat we live in a world that is profoundly interconnected.In an age of Brexit and Trump, the themes of isolation andfragmentation permeating the Western world stand in sharp contrast to events along the Silk Roads since 2015, where ties have been strengthened and mutual cooperation established. With brilliant insight, Peter Frankopan takesa fresh look at the network of relationships being formed along the length and breadth of the Silk Roads today, assessing the global reverberations of these continual shifts in the centre of power - all too often absent from headlines in the West. This important - and ultimately hopeful - book asks us to re-read who we are and where we are in the world, illuminating the themes on which all ourlives and livelihood depend.
The roads to the East -- The roads to the heart of the world -- The roads to Beijing -- The roads to rivalry -- The roads to the future.
Includes bibliographical references and index.
Keywords: Asian cooperation; East and West; Asia -- Foreign economic relations; Asia -- Economic integration; Asia -- Economic conditions -- 21st century